Tinjauan Total Quality Management (TQM) Pada Lembaga Pendidikan Islam - Wahyu Septiadi (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2019)
In the context of progress and the development of management quality in an institution especially in Islamic education institutions in order to improve the quality and quality of islamic education, it is very interesting matter to be studied together. The many phenomena surrounding the success of an Islamic education institution is a challenge for other educational developers to continue to compete in improving the overall quality of management. Total Quality Management is a management concept that is oriented towards improving quality and customer satisfaction for the service provided. Total Quality Management, or integrated quality management, is a paradigm of continuous quality improvement by presenting a set of practical tools to each educational institution in meeting the needs and satisfaction of its customers in the present and in the future. The advantages of TQM lie in the planning system. In the TQM planning process will be carried out with active involvement and full commitment and high consistency from all members of the organization. The evaluation process on TQM will also be carried out maximally through emphasis on the purpose of achieving the TQM goals. Evaluation is also carried out as a form of continuous reflection followed by supervision and ultimately focuses on quality assurance for customer satisfaction. This paper tries to explain the results of the TQM concept review as an information in a management system that might be implemented in an Islamic education institution, as well as other educational institutions.